The impact of Iraqi women watching foreign TV series on their behavior (Journal of Imam Al-Kadhim College, 2025)
The research aims to identify the level, reasons and reflection of Iraqi women's viewing of imported series on satellite channels on their general behavior. The research was conducted on a sample of Iraqi women from Baghdad Governorate, consisting of (373) individuals, according to the "multi-stage random samples" method. The researcher used the survey method through the questionnaire and scale tools to collect data and information. The statistical results showed that Iraqi women watch imported series on average through satellite channels, and feel that these series are trying to instill values ​​and behaviors that are strange to the Iraqi family. They contain stories and scenes of relationships between men and women that are illegitimate and unacceptable in our societies, in addition to the undesirable mixing between men and women to work in liquor bars and nightclubs. It was indicated that this behavior is inconsistent in one way or another with the ethics of Iraqi society. The results also indicated that Turkish series are at the forefront of viewing over the rest of the series dubbed in the Syrian or Lebanese dialect.
Keywords: Reflection, Viewing, Iraqi Women, Foreign TV Series, Behavior